Masyarakat dalam Keragaman (Analisis Konflik Dan Pemecahannya) - Vialinda Siswati (FALASIFA : Jurnal Studi Keislaman, 2017)
The purpose in writing this article to provide understanding of the community about diversity in both thinking and being faced with others, this often leads to conflict, the conflict can be non existence or unreal conflik these two things if entering certain circles and not immediately resolved it will arise disintegration So that the degradation of unity and unity appears to be a matter that has begun to be taken seriously by the government, triggering the emergence of new policies at the current level of the Act, the author of this article tries to make a contribution from a different perspective by giving the community the meaning of plurarism, Multiculturalism and integration that is considered a necessity with its own limitations so that the wider community especially the academicians can understand the diversity and attitude that should be taken.Keywords:Masyarakat,Keragaman,Konflik